"Salmond's Bench": The New Zealand Supreme Court Judiciary 1920-1924 - Morris, Grant (Victoria University of Wellington Law Review, 2008)
John Salmond dominated the New Zealand legal environment during the early twentieth century. Salmond performed many roles in the New Zealand legal system. This article focuses on his final legal role, as a Supreme Court judge, and looks at the nature of the Supreme Court Bench from 1920 to 1924. Some of New Zealand's greatest legal names sat with Salmond during this time. Twentieth century New Zealand legal history is a relatively unexplored area and requires more attention from historians. This article provides the basis for possible future work on the Supreme Court Bench during the early 1920s. In discussing the nature of "Salmond's Bench" the backgrounds of the different Supreme Court justices are explored. Following this, selected cases are analysed revealing distinctive factors relating to how this group of judges worked together and the nature of their judgments. Particular attention is paid to the divisions on the Bench regarding the crucial social issue of divorce. Viewing the decisions made by Salmond's Bench in the context of the political and social backgrounds of the judges and the historical background of this period provides a vital third dimension to the judgments. Salmond's distinctive approach to judicial decision-making becomes clearer when directly compared with the approaches of his judicial peers.